Options for Care of Elderly Inpatients With Chronic Diseases: Analysis of Distribution and Factors Influencing Use of Care in Shanghai, China - Shi, Jianwei; Chen, Ning; Liu, Nana; Yang, Yan; Yu, Dehua; Jin, Hua; Luo, Li; Gong, Xin; Liu, Qian; Chen, Chen; Yu, Wenya; Wang, Zhaoxin (Frontiers in Public Health, 2021)
Background: China’s ability to provide sufficient healthcare for an elderly population with chronic diseases has become a challenge because of poor utilization of different levels of medical institutions. We aimed to explore the characteristics and factors influencing patient choices and the resulting utilization of different levels of public medical institutions among elderly inpatients with chronic diseases. Methods: Data were collected from the Information Center of the Health and Family Planning Commission of Pudong New Area in Shanghai from 2013 to 2016. A cross-sectional study using multinomial logistic regression analysis was performed to find the factors influencing use of care. Records of patients were identified from electronic health records from public medical institutions. Results: There were 95,445 elderly inpatients with chronic diseases in public medical institutions, 17.78% in community health centers, 68.44% in secondary hospitals, and 13.78% in tertiary hospitals. Compared with those over 80 years old, the 60-69 age group showed a preference for secondary hospitals (OR=2.980, P<0.001) and tertiary hospitals (OR=4.497, P<0.001), a trend also observed in the 70-79 age group (OR=1.353, P<0.001; OR=1.673, P<0.001). Compared with those using urban employee basic medical insurance, inpatients using urban resident basic medical insurance were less likely to visit secondary hospitals than community health centers (OR=0.237, P<0.001) or tertiary hospitals (OR=0.293, P<0.001). Compared with those inpatients who were married, inpatients who were widowed were less likely to go to secondary hospitals (OR=0.391, P<0.001) or tertiary hospitals (OR=0.045, P<0.001) than community health centers. Conclusions: The utilization of different levels of medical institutions by elderly people is not well-suited to the respective functions of these medical institutions. Most care services should be provided by community health centers, but our findings indicate that elderly people are more inclined to seek inpatient care at secondary hospitals and tertiary hospitals with some variation based on the patients’ sex, age, medical insurance, expenses, and expected length of stay.